THE ROLE OF MUSIC TO TEACHING FOREIGN LANGUAGE - Ashuraliyeva Mohira; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Music helps people learn things. Think about the songs your teachers taught you to memorize multiplication tables, commercials that sing out their phone numbers on television, etc.